The Influence of Transformational Leadership on Organizational Citizenship Behavior Through Mediation of Job Satisfaction - Alfira Tri Andiningtyas; Ali Imron; Enis Khaerunnisa (Indonesian Journal of Innovation Multidisipliner Research, 2025)
This study aims to investigate and analyze the relationship between Transformational Leadership and Organizational Citizenship Behavior with job satisfaction as a mediating factor among employees at PT Hi-Lex Indonesia Tangerang. This type of research uses quantitative research with 75 samples and use simple random sampling technique. Data collection techniques in this study include observation, interviews, and the distribution of questionnaires. The data analysis was conducted using the Smart Partial Least Square 4.0 (SmartPLS) application. The results indicate that transformational leadership has a positive and significant effect on OCB, transformational leadership has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on OCB, and job satisfaction positively and significantly mediates the effect of transformational leadership on OCB.